2015
DOI: 10.1002/jsfa.7159
|View full text |Cite
|
Sign up to set email alerts
|

Generation and identification of anti‐inflammatory peptides from bovine β‐casein using enzyme preparations from cod and hog

Abstract: The more chymotryptic enzyme activity is present, the lower is the potential anti-inflammatory activity of the hydrolysates in HEK(nfκb-RE) cells. Comparable peptides were produced by application of porcine trypsin (TPCK) and cod trypsin. Therefore, the enzyme preparation cod trypsin can replace the non-food-grade porcine enzyme preparation trypsin (TPCK) for the generation of potential anti-inflammatory peptides from β-casein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It was suggested that a group of large hydrophobic peptides were responsible for the antiinflammatory activity. The hydrolysis of β-casein using cod trypsin has also been reported to have anti-inflammatory activity in kidney cells and larger peptides (> 5 kDa) were reported to have higher activity compared with lower molecular mass peptides (Altmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that a group of large hydrophobic peptides were responsible for the antiinflammatory activity. The hydrolysis of β-casein using cod trypsin has also been reported to have anti-inflammatory activity in kidney cells and larger peptides (> 5 kDa) were reported to have higher activity compared with lower molecular mass peptides (Altmann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The antiinflammatory activity of all seven hydrolysate 5 kDa permeates may be linked to NF-κB activation as the protein expression of p65 was inhibited in all cases. Milk-derived hydrolysates with anti-inflammatory activity have previously been reported to act through the NF-κB pathway in different cell lines (Altmann et al, 2016;Malinowski et al, 2014;Marcone, Haughton, Simpson, Belton, & FitzGerald, 2015;Nielsen, Theil, Larson, & Parup, 2012). To the best of our knowledge, our study is the first to examine the molecular mechanism behind the anti-inflammatory activity of bovine casein hydrolysates in macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These peptides may affect the cardiovascular (casokinins, casoplatelins), nervous (antagonists and agonists of opiate receptors), immune (immunomodulators) and digestive (regulators of motility and secretion in the gastroenteric tract, metal-binding peptides) systems. New kinds of biological action of casein peptides are discovered [4,5]. Casein belongs to heterogeneous proteins and consists of four basic (α S1 -CN, α S2 -CN, β-CN and κ-CN) and numerous minor fractions.…”
mentioning
confidence: 99%
“…However, capability of such hydrolysates to target ENS maturation has never been investigated. Therefore, we analyzed the potential of a recently characterized bovine tryptic β-CN hydrolysate presenting anti-inflammatory properties (Altmann et al, 2016) to nutritionally target ENS development.…”
mentioning
confidence: 99%